2010
DOI: 10.1002/jbm.a.32782
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance and in vitro response of laser‐deposited Ti‐Nb‐Zr‐Ta alloys for orthopedic implant applications

Abstract: While direct metal deposition of metallic powders, via laser deposition, to form near-net shape orthopedic implants is an upcoming and highly promising technology, the corrosion resistance and biocompatibility of such novel metallic biomaterials is relatively unknown and warrants careful investigation. This article presents the results of some initial studies on the corrosion resistance and in vitro response of laser-deposited Ti-Nb-Zr-Ta alloys. These new generation beta titanium alloys are promising due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 15 publications
5
28
0
Order By: Relevance
“…Based on the results of electrochemical impedance spectroscopy it was suggested that a bilayer passive film was formed after oxidation of the Ti-29Nb-13Ta-4.6ZrTZ alloy at 1.0 V in Hanks' physiological solution [23]. The behaviour of the Ti-35Nb-7Zr-5Ta alloy was comparable to that of Ti-6Al-4V in Ringer solution [24].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of electrochemical impedance spectroscopy it was suggested that a bilayer passive film was formed after oxidation of the Ti-29Nb-13Ta-4.6ZrTZ alloy at 1.0 V in Hanks' physiological solution [23]. The behaviour of the Ti-35Nb-7Zr-5Ta alloy was comparable to that of Ti-6Al-4V in Ringer solution [24].…”
Section: Introductionmentioning
confidence: 99%
“…During the past few decades, interest in titanium alloys has been continuously increasing due to their combination of properties such as high strength [1][2][3][4][5][6], low density, biocompatibility [7][8][9][10] and good corrosion resistance [11,12]. However, both their low ductility (uniform elongation typically less than 0.20) and their lack of strain-hardening when compared with steels or Co-Cr alloys [11,13] limit their use in advanced applications where superior combinations of strength and ductility are required.…”
Section: Introductionmentioning
confidence: 99%
“…However, the possibility that TNTZ coating on Ti-6Al-4V hip prostheses can improve the latter's performance should be considered a promising one. According to reports in the literature [23][24][25] , new β-type TNTZ alloys present mechanical and biochemical properties that render them suitable for application as prosthetic coatings or in the prosthetic stem itself. Of course, accreditation by a competent agency is required and certification may take some time.…”
Section: Resultsmentioning
confidence: 99%